RELATIVE PALATABILITY BY SHEEP AND GOATS OF OVEN-DRIED CALLIANDRA, ALBIZIA, GLIRICIDIA, AND LEUCAENA LEAVES - KARDA, I W.; SPUDIATI, SPUDIATI (Fakultas Peternakan Universitas Udayana, 2006)
SUMMARY This experiment was conducted to assess the palatability of the lesser known fodder trees such as calliandra, and albizia which may have potential to be included in farming systems in the tropics the experiment. It was conducted in The University of Queensland, Gatton College in 1996 using six sheep and six goats in a Latin Square design involving pair-wise comparisons of four types of fodder trees, calliandra, albizia, gliricidia and leucaena. Variables measured were intake rates of each of fodder tree examined and differences between means were examined by the general linear model procedure of the Statistical Analysis System. The results showed that the overall intake rate of tree leaves examined was affected by animal species (P<0.0017) and tree types (P< 0.001). Rates of intake of gliricidia were consistently low and those of leucaena were consistently high, by both species of animals. Goats ate more quickly overall than sheep, but both species ate gliricidia much less rapidly than the others. Rates of intake of both calliandra and albizia were altered by the type of leaf fed as the pair. Intakes of calliandra were faster when paired with gliricidia than with albizia, and were reduced further when paired with leucaena. Rates of albizia intake were similarly influenced by the fodder which was paired with it. Fodder trees can be ranked with increasing order of palatability such as gliricidia, calliandra, albizia and leucaena.